ISLAMIC EDUCATION TRANSFORMATION MANAGEMENT THROUGH INTEGRATION OF TRADITIONAL AND MODERN EDUCATION IN CHARACTER BUILDING OF INDEPENDENT STUDENTS - Intan Kumala Sari; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the management strategy of Islamic education transformation in integrating traditional and modern education systems and to determine its contribution to the development of independent character of students management of Islamic education transformation through the integration of traditional and modern education in the formation of independent character of students. This study uses a qualitative method with a library research approach through a review of various literature, scientific journals, and references relevant to Islamic education management, Islamic boarding school integration, and character education. Data analysis was conducted descriptively through the stages of data reduction, information grouping, interpretation, and drawing conclusions. The results show that the transformation of Islamic boarding school education is carried out through a change management strategy that maintains traditional values such as the study of yellow books, the role model of kiai, moral development, and Islamic boarding school culture, and integrates them with a modern education system in the form of curriculum development, technology, and skills. This integration contributes to the formation of independent character of students through the habituation of discipline, responsibility, self-management skills, and leadership. This study concludes that the management of Islamic education transformation that balances traditional and modern values can make Islamic boarding schools into adaptive, quality educational institutions, and remains based on Islamic values.